(untitled) (Contemporary Central & East European Law, 2024)
Administrative power is an attribute of public administration which is a reflection of state power. Thanks to it, the administration can unilaterally shape the legal situation of the administered persons, exercising the powers granted to it. However, the scope and manifestations of power must be regulated in statutes, which is a prerequisite for exercising control over the administration in a democratic state ruled by law. The functions, goals and tasks of the administration evolve, the intensity and manifestations of administrative power also change, yet it is still a permanent feature of administration and there is no indication that this will change. The article shows the evolution of power in various manifestations of administration activity, both in legal and factual activities. The changing models of the administrative procedure and, consequently, the degree of intensification of the authoritative actions in the classical sense of authority in the issuance of administrative acts were analysed. The characteristic types of authority were also indicated, such as: planning authority, statutory authority, organizational and functional authority, plant authority.